The role of civil society institutions in community development.Field study (community institutions in the municipality of Tragin( (Journal of Human Sciences, 2024)
Civil society organizations contribute to highlighting their role in economic, social, political and security activities, and in the development of the local community in the municipality of Tragin, and civil society organizations in Libya face many difficulties, the most important of which is the lack of clarity and agreement on goals and the difficulty of achieving them.The importance of this study emerges by highlighting the role of civil society institutions in the development of local communities, through what they provide theoretically and realistically to understand the reality of the role of these institutions in development and the extent of their contribution to the development of the local community, and to identify the degree of practicing voluntary humanitarian work among their employees, and the current study aims to identify the reality of the role of civil society institutions in developing local communities in the municipality of Tragin in southern Libya in particular, to identify the most important obstacles facing civil society institutions in Libyan society in general, and to identify the mechanisms that lead to activating the role of civil society institutions In order to achieve the objectives of this study and answer its questions, it relied on the use of the descriptive method and the social survey method with a sample, and this study is considered one of the descriptive studies, and this study also relied on questionnaire forms as the main tool for data collection, and used a simple random sample consisting of (80) single females and males working in civil society organizations in the municipality of Tragin, and the study relied on the observation and personal interview method with the sample members.It is clear from the results of the study that civil society institutions in the municipality of Tirghin have a great role in bringing about change and local development through the programs and activities they provide, despite the existence of some obstacles and difficulties that may contribute to delaying their role in development.